The determinants of rice farmers’ productivity in Ekiti State, Nigeria (2016)
The issue of low productivity of the Nigerian farmers is becoming topical particularly in rice production. Rice is an annual crop and one of the most important staple food crops in Nigeria. Since the mid-1970, the demand for rice has been increasing at a much faster rate in Nigeria than in any other African country. This paper therefore examines the factors affecting rice farmers’ productivity as well as constraints limiting rice production in Ekiti State, Nigeria. Primary data was used for this study with the aid of a well-designed questionnaire to collect data from 160 randomly selected rice farmers. A multi-stage random sampling procedure was used in selecting the respondents. Three major rice-producing Local Government Areas (LGAs) were purposively selected from the State, followed by the random selection of two villages from each LGA. In all, 160 rice farmers were randomly selected from six villages. The objectives were analysed using descriptive statistics, OLS regression and Likert-type scale. The results showed that the linear functional form gave the best line of fit. R2 value was about 77% and statistically significant at 1% level. Farm size, level of education and quantity of fertilizer were positively and significantly related to productivity at 1% and 10% respectively, while years of farming experience and quantity of seeds used were negatively significant at 10% and 1% respectively. Pest infestations and financial constraints were ranked as the most challenging factors limiting rice production in the study area. It is therefore recommended that extension services should be intensified in the area to educate the farmers on the appropriate application rate of fertilizer and seed rate per hectare. In addition, the relevant research institutes should develop a technology for controlling or preventing birds’ infestations in the area.